2020
DOI: 10.1051/0004-6361/202039250
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Hyades, the eclipsing binary HD 27130, and the oscillating red giant ϵ Tauri

Abstract: Context. The derivation of accurate and precise masses and radii is possible for eclipsing binary stars, allowing for insights into their evolution. When residing in star clusters, they provide measurements of even greater precision, along with additional information on their properties. Asteroseismic investigations of solar-like oscillations offers similar possibilities for single stars. Aims. We wish to improve the previously established properties of the Hyades eclipsing binary HD 27130 and re-assess the as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…This has been exploited in both globular clusters (e.g., Brogaard et al 2017;Kaluzny et al 2014Kaluzny et al , 2015Thompson et al 2010Thompson et al , 2020 and open clusters (e.g., Brogaard et al 2011;Kaluzny et al 2006;Knudstrup et al 2020;Meibom et al 2009;Sandquist et al 2016;Torres et al 2020). However, sometimes the eclipsing systems found are on the main sequence, which still allows some model constraints, but not on the age (e.g., Brogaard et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This has been exploited in both globular clusters (e.g., Brogaard et al 2017;Kaluzny et al 2014Kaluzny et al , 2015Thompson et al 2010Thompson et al , 2020 and open clusters (e.g., Brogaard et al 2011;Kaluzny et al 2006;Knudstrup et al 2020;Meibom et al 2009;Sandquist et al 2016;Torres et al 2020). However, sometimes the eclipsing systems found are on the main sequence, which still allows some model constraints, but not on the age (e.g., Brogaard et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found eclipsing binaries in stellar associations whose ages are known. These are the cases of M11, a ∼200 Myr old open cluster (see the case of KV29, a massive system Bavarsad et al 2016); the Hyades, which is 625-790 Myr, and several interesting systems (HD 27130, which has a solarlike primary by Brogaard et al 2021, andvA 50, a M4 plus, perhaps, a planet David et al 2016); Praesepe, which is 600-800 Myr (several M-type binaries; Gillen et al 2017); several young stellar associations such as UpperSco, 5-10 Myr (USco J161630.68-251220.1, a M 5.5 primary with a very low-mass star close to the substellar limit, Lodieu et al 2015; or the transiting brown dwarf RIK 72 b, David et al 2019), or the first ever discovered eclipsing binary brown dwarfs, which is located in the 1 Myr massive association in Orion (Stassun et al 2006); and in globular clusters, such as NGC 6362, a 11.67 Gyr association that includes V40, a solar-like pair (Kaluzny et al 2015).…”
Section: Eclipsing Brown Dwarf Inflated By Its Subgiant Hostmentioning
confidence: 99%
“…Several studies have found eclipsing binaries in stellar associations whose ages are known. These are the cases of M11, a ∼200 Myr old open cluster (see the case of KV29, a massive system Bavarsad et al 2016); the Hyades, which is 625-790 Myr, and several interesting systems (HD 27130, which has a solarlike primary by Brogaard et al 2021, andvA 50, a M4 plus, perhaps, a planet David et al 2016); Praesepe, which is 600-800 Myr (several M-type binaries; Gillen et al 2017); several young stellar associations such as UpperSco, 5-10 Myr (USco J161630.68-251220.1, a M5.5 primary with a very low-mass star close to the substellar limit, Lodieu et al 2015; or the transiting brown dwarf RIK 72 b, David et al 2019), or the first ever discovered eclipsing binary brown dwarfs, which is located in the 1 Myr massive association in Orion (Stassun et al 2006b); and in globular clusters, such as NGC 6362, a 11.67 Gyr association that includes V40, a solar-like pair (Kaluzny et al 2015).…”
Section: Eclipsing Brown Dwarf Inflated By Its Subgiant Hostmentioning
confidence: 99%